United States. Army. Office of the Judge Advocate General records - United States. Army. Office of the Judge Advocate General
Letterpress copies of letters written chiefly to Levi C. Turner, judge advocate, by Reuben Hitchcock and Samuel Galloway, special commissioners appointed by U.S. secretary of war Edwin M. Stanton to hear and determine the cases of state prisoners at Camp Chase, Ohio, during the Civil War. The letters relate chiefly to prisoners charged with disloyal activities, largely in Kentucky, but also in Alabama, Missouri, Ohio, Tennessee, and Virginia. Other recipients of letters include Joseph Darr, Jr., provost marshal general of Virginia, Francis Pierpont, Union governor of Virginia, David Tod, governor of Ohio, and Peter Zinn, commandant of Camp Chase.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Keywords: Darr, Joseph -- Correspondence; Galloway, Samuel, -- 1811-1872 -- Correspondence; Hitchcock, Reuben -- Correspondence; Pierpont, Francis Harrison, -- 1814-1899 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869.; Tod, David, -- 1805-1868 -- Correspondence; Turner, Levi C., -- -1867 -- Correspondence; Zinn, Peter -- Correspondence; Camp Chase (Ohio); Alabama -- History -- Civil War, 1861-1865.; Kentucky -- History -- Civil War, 1861-1865.; Missouri -- History -- Civil War, 1861-1865.; Ohio -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Virginia -- History -- Civil War, 1861-1865.